The Influence of Profitability and Industry Sensitivity on Disclosures of Modern Slavery Listed on the Indonesian Stock Exchange - Desy Mayasari; Susi Sarumpaet; Usep Syaipudin (Cita konsultindo, 2024)
Accounting researchers' interest in modern slavery grew following the introduction of the California Transparency in Supply Chains Act (2010), which requires retail sellers and manufacturers doing business in California to disclose their efforts to eradicate slavery and human trafficking from their direct supply chains. However, disclosure of modern slavery in Indonesia is still voluntary. The aim of this research is to see how profitability and industry sensitivity influence the disclosure of modern slavery in Indonesia, which is still voluntary. The population in this study were all companies actively listed on the Indonesia Stock Exchange during 2020-2022, totaling 890 companies. The sample used was 657 companies selected using the purposive sampling method. This research uses secondary data obtained from annual reports published on the official website of the Indonesian Stock Exchange and the company's official website. Data analysis techniques use descriptive statistics and multiple linear regression. The results of this research indicate that profitability and industry sensitivity partially have a positive and significant effect on the disclosure of modern slavery. Simultaneously, the results of this research show that profitability and industry sensitivity have a positive and significant effect on the disclosure of modern slavery.